A Bibliometric Study on Students’ Theses at the Department of Elementary School Teacher Education, Universitas Negeri Makassar - Masni Masni (Literatify: Trends in Library Developments, 2020)
Bibliometrics is a scientific study of which one of the benefits is predicting the development of a scientific discipline. This bibliometrics study is intended to find out what research themes and subjects are often used as thesis research topics for students of the Department of PGSD, Makassar State University. Bibliometrics research uses a statistical approach in measuring bibliography which in this case is a thesis. The population in this study is the title of student theses for the period 2017-2018 with a total sample of 338 thesis titles. Data collection techniques are done through documentation that is analyzed using a simple statistical formula. The results showed that subjects that were often used as research themes by PGSD majors were learning methods, namely 198 thesis titles with a percentage of 58.58% of the total sample. While for subjects that are often used as research objects are 114 Natural Sciences thesis titles with a percentage of 33.73% of the total sample. ABSTRAKBibliometrika merupakan kajian keilmuan yang salah satu manfaatnya ialah memprediksi perkembangan suatu disiplin ilmu. Kajian bibliometrika ini dimaksudkan untuk mengetahui tema penelitian dan subjek apa saja yang sering dijadikan sebagai topik penelitian skripsi mahasiswa Jurusan PGSD, Universitas Negeri Makassar. Penelitian bibliometrika menggunakan pendekatan statistika dalam mengukur bibliografi yang dalam hal ini ialah skripsi. Populasi dalam penelitian ini adalah judul skripsi mahasiswa periode tahun 2017-2018 dengan jumlah sampel sebanyak 338 judul skripsi. Teknik pengumpulan data dilakukan melalui dokumentasi yang dianalisis menggunakan rumus statistik sederhana. Hasil penelitian menunjukkan bahwa subjek yang sering dijadikan tema penelitian oleh mahasisiwa jurusan PGSD adalah Metode Pembelajaran yakni sebanyak 198 judul skripsi dengan persentase sebesar 58,58% dari total keseluruhan sampel. Sementara untuk mata pelajaran yang sering dijadikan objek penelitian adalah mata pelajaran IPA sebanyak 114 judul skripsi dengan persentase sebesar 33,73% dari total sampel.